TAXONOMY AND PRESENT DISTRIBUTION OF DIFFERENT SPECIES OF CAREXL., CYPERACEAE IN DARJEELING AND SIKKIM HIMALAYAS, INDIA : Life Science-Botany - GHOSH, ASOK; GAURGOPAL MAITI (International Journal of Life Science and Pharma Research, 2014)
Study of the genus Carex L. was performed based on 23 species, including 2 varities, collected from Northeastern India, mostly from the Sikkim Himalaya and Darjeeling Himalaya of Darjeeling district of West Bengal, during 2006 to 2010. In all the cases life-specimens were studied in the field itself for habit and habitat nature and in this regards several populations had been regularly observed. Beside these a few previous collections were taken into consideration from the other states of North-eastern India for the study of floral biology. Most of the morphological characters of vegetative organs were studied in the field as in-situ condition and the morphological features of reproductive organs were studied in the laboratory. For each species a number of populations and a good number of specimens were examined. Based on the characters studied all these collected specimens were identified properly and the correct nomenclature of each species is provided. The inflorescence pattern i.e. the synflorescence, pseudoflorescence, spikes, peduncles, distribution of the sexes in a spike, ratio of the distribution of sexes was studied for each species of Carex. The analysis of inflorescence nature, from simple to complex synflorescence nature was thoroughly discussed. The arrangements of different types of floral glumes as male, female and sterile ones were thoroughly studied. The appendages in anthers are also important features of interest as like the stigma and the apices of glumes. Each species were arranged accordingly followed by the key to the species. As a whole this study is provided with field observations of species and population, study of different morphological macrocharacters, the study of light microscopic features of floral biology, microscopic study of utricles and nuts including the silica bodies. Besides the observations a general discussion is provided for the genus Carex.